Analysis of target radar cross-section using CST software / Mohd Nizamuddin Abd Latif - Abd Latif, Mohd Nizamuddin (2013)
This project intends to design and analyze a target radar cross-section and far-field simulation for radar application by using CST MWS software. FSR enhanced a radar target cross-section and more reliability to detect and track target compared to conventional radar. The simulations indicate different radar target and its simulation. The radar target model are designed with exact size as real car from Perodua blueprint .The comparison of radar cross-section between the different type of car model with different frequencies and target position are been analyzed. The radar target are simulated with a different frequencies which are 64Mhz, 150Mhz and 400Mhz. Different angle of planar wave propagate will resulting different radar cross-section and far-field region to radar target. .